KAJIAN ETNOBOTANI TUMBUHAN RITUAL SUKU TAJIO DI DESA KASIMBAR KABUPATEN PARIGI MOUTONG - Rahyuni, Rahyuni; Yniati, Eny; Pitopang, Ramadhanil (Natural Science: Journal of Science and Technology, 2013)
Ethnobotanic Study of Tajio Tribe Ritual Plants at Kasimbar Village, Parigi Moutong Regency was conducted from December 2012 until February 2013. The objective of this study was to know kinds of plants, meaning of them, and ways of taking advance of them by people of Tajio tribe. The research methods used were the combination between qualitative methods. They were observation, moderaate participatory, purposive sampling and snowball sampling, and 102 items of questionnaire for respondents. The plants were used for tradition ritual on Tajio tribe like wedding, house building, rice planting, birth and religious events. The result showed that based on the habitat, there were 7 species of trees, 3 clusters of clumps, 11 clusters of bushes, 16 categorized herbs and 4 kinds of categorzed lily used for the traditional ritual. In addition, based on parts of the plants, there were 8 species of roots, 15 species of stems, 15 species of leaves, 11 species of fruit, 5 species of flowers, 4 species of seeds, 3 species of tubers and 2 species of plant players.